Indo-Pacific Role in Iran’s East Look Strategy - Mohammad Reza Mohammadi (Relaciones Internacionales)
After the collapse of the Soviet Union and the end of the Cold War, many countries with a multidimensional and strategic view of regionalism and related issues paid special attention to securing, guaranteeing, and maximizing their national interests. Following the international developments that emerged in the atmosphere after the 1979 revolution, the political elites of the Islamic Republic of Iran —taking into account the historical experience and the cold relations with the West— tried to create deep political and economic constructive cooperation and interaction based on the East Look strategy with resource centers and revisionist countries in competition with America’s new order. This approach was reflected in official documents such as the Twenty-Year Vision, General Policies document approved by the Assembly, the Expediency Discernment Council and the Constitutional Law.